2018
DOI: 10.1038/s41598-018-23740-5
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA (eDNA) detects the pool frog (Pelophylax lessonae) at times when traditional monitoring methods are insensitive

Abstract: Detection of endangered species is invaluable for conservation efforts, yet many traditional sampling techniques are ineffective at low population abundances or during certain periods of the year. Here, we compared results from a newly developed eDNA approach and the traditional observational method for the endangered pool frog (Pelophylax lessonae). Analysis using an occupancy-modeling framework indicated that the probability of pools being occupied using eDNA (0.93) was higher than for the traditional method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 34 publications
4
46
1
1
Order By: Relevance
“…Our estimates of 84% detection probability using eDNA compared to 28% for conventional sampling methods suggest that eDNA is a highly effective method to detect hellbender presence. Furthermore, our results are consistent with other eDNA studies that report higher detection estimates than conventional sampling methods (Eiler, Löfgren, Hjerne, Nordén, & Saetre, 2018;Jane et al, 2015;Schmelzle & Kinziger, 2016;Schmidt, Kery, Ursenbacher, Hyman, & Collins, 2013). Thus, the effectiveness of eDNA as a tool for detecting rare, cryptic, or threatened species has wide ranging implications for the monitoring, conservation, and management of these species.…”
Section: Detection Probabilitiessupporting
confidence: 90%
See 2 more Smart Citations
“…Our estimates of 84% detection probability using eDNA compared to 28% for conventional sampling methods suggest that eDNA is a highly effective method to detect hellbender presence. Furthermore, our results are consistent with other eDNA studies that report higher detection estimates than conventional sampling methods (Eiler, Löfgren, Hjerne, Nordén, & Saetre, 2018;Jane et al, 2015;Schmelzle & Kinziger, 2016;Schmidt, Kery, Ursenbacher, Hyman, & Collins, 2013). Thus, the effectiveness of eDNA as a tool for detecting rare, cryptic, or threatened species has wide ranging implications for the monitoring, conservation, and management of these species.…”
Section: Detection Probabilitiessupporting
confidence: 90%
“…Our results are consistent with Spear et al (2015), who found that eDNA sampling outperformed conventional surveys for hellbenders. Furthermore, our results are consistent with other eDNA studies that report higher detection estimates than conventional sampling methods (Eiler, Löfgren, Hjerne, Nordén, & Saetre, 2018;Jane et al, 2015;Schmelzle & Kinziger, 2016;Schmidt, Kery, Ursenbacher, Hyman, & Collins, 2013). Estimating detection probabilities from multiple site visits accounts for false negatives (i.e., when the animal is present at a site but goes undetected; MacKenzie et al, 2002).…”
Section: Detection Probabilitiessupporting
confidence: 90%
See 1 more Smart Citation
“…Our environmental DNA results imply the presence of fish species that have not yet been verified using traditional fishing methods, including a number of non-native species (Table 1 ). This is not surprising given the size of these water bodies, the sensitivity of eDNA surveys 71 , 72 , and the fact that aquaculture 73 and the exotic fish trade 74 are common in China. Two other considerations bear on our results.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental DNA (eDNA) surveys continue to gain popularity for detecting invasive, cryptic and rare species (Klymus, Richter, Chapman, & Paukert, 2015; Lodge et al., 2012; Schmelzle & Kinziger, 2016; Sepulveda et al., 2019), as these techniques are often easier, less expensive and more sensitive than non‐molecular detection tools (Eiler, Löfgren, Hjerne, Nordén, & Saetre, 2018; Hunter, Meigs‐Friend, Ferrante, Smith, & Hart, 2019; Sengupta et al., 2019; Sepulveda et al., 2019; Williams, Huyvaert, Vercauteren, Davis, & Piaggio, 2018). These surveys rely on hierarchical sampling techniques to accommodate spatial heterogeneity in the occurrence of DNA within a study region.…”
Section: Introductionmentioning
confidence: 99%